Insulin secretion improves in cystic fibrosis following ivacaftor correction of CFTR: a small pilot study. Issue 6 (13th March 2013) - Bellin, Melena D; Laguna, Theresa; Leschyshyn, Janice; Regelmann, Warren; Dunitz, Jordan; Billings, JoAnne; Moran, Antoinette
Abstract Objective To determine whether the cystic fibrosis (CF) transmembrane conductance regulator (CFTR) is involved in human insulin secretion by assessing the metabolic impact of the new CFTR corrector—ivacaftor. Methods This open‐label pilot study was conducted in CF patients with the G551D mutation given new prescriptions for ivacaftor. At baseline and 4 wk after daily ivacaftor therapy, intravenous glucose tolerance tests (IVGTT) and oral glucose tolerance tests (OGTT) were performed. Results Five patients aged 6–52 were studied. After 1 month on ivacaftor, the insulin response to oral glucose improved by 66–178% in all subjects except one with long‐standing diabetes. OGTT glucose levels were not lower in the two individuals with diabetes or the two with normal glucose tolerance (NGT), but the glucose tolerance category in the subject with impaired glucose tolerance (IGT) improved to NGT after treatment. In response to intravenous glucose, the only patient whose acute insulin secretion did not improve had newly diagnosed, untreated CFRD. The others improved by 51–346%. Acute insulin secretion was partially restored in two subjects with no measurable acute insulin response at baseline, including the one with IGT and the one with long‐standing diabetes. Conclusions This small pilot study suggests there is a direct role of CFTR in human insulin secretion. Larger, long‐term longitudinal studies are necessary to determine whether early initiation of CFTR correction, particularly in young children with CF who have not yet lost considerable β‐cell mass, will delay or prevent development of diabetes in this high‐risk population.